Overcoming the unique history: Heritage education as an instrument of cultural democratization in the Federal District (Cadernos de Sociomuseologia, 2020)
This article aims to reflect on the challenges and potential of heritage education in the context of the Federal District from a sociomuseological perspective. Considering that memory is the foundation for the construction of social identity and that this process is permanently redefined in the dialogical relationship with the other, heritage and museums are important instruments to reestablish these dialogues of diversity. In the face of museums and cultural spaces that reiterate the consecrated discourse about the construction of Brasilia, privileging specific names and facts, how to effectively enforce the relationship between heritage, identity and citizenship? I seek through experience as an educator in a cultural space to reflect on perceptions, potentialities and approaches that aim to overcome the unique history including other voices in this relationship in view of an education for autonomy and cultural democratization. Key Words: Heritage. Heritage Education. Cultural Diversity. Brasília. Federal District.